G-net 2000 :a network management system for UNIMAS virtual campus - Subramaniam, Gokula Krishnan (Universiti Malaysia Sarawak, UNIMAS, 2001)
With the introduction of Information, Communication and Technology (ICT) in education, a new paradigm in learning called E-learning has replaced the conventional method of education. E-learning, which is the key entity of the UNIMAS Virtual Campus, relies on a networked computer environment to facilitate communication between knowledge providers and knowledge seekers.